Information transparency of state bodies as a criterion of public administration efficiency - Bekbossynova, Zh.A.; Junusbekova, G.A. (BUKETOV BUSINESS REVIEW, 2019)
In the article areas of improvement, increase of the efficiency of the state apparatus are considered, one of which is informational openness, transparency of the activities of state bodies to the population of the country. This direction provides the citizens of the state with the right to involvement and participation in the adoption and implementation of state and strategic policy documents. The study provides an expert assessment of the degree of openness and transparency of the activities of each government body. Transparency, accountability and openness of the state imply that any non-secret information owned by state bodies should be available and provided to citizens of the country. Openness of activity is carried out through the publication of strategic and program documents, information, news, reports, articles of first leaders, reports on the work done, for a certain period, etc. in the media and on the official Internet resources (websites) of state bodies. These requirements are spelled out in the Rules for the Information Content of Internet Resources of Government Agencies and the requirements for their content approved by order of the Minister for Investment and Development of the Republic of Kazakhstan. In the study of the websites of the central state bodies and local executive bodies, certain tendencies and patterns in the formation of the information openness of the state bodies of the country were shown.